Spasial Analysis of Pulmonary Tuberculosis Transmission Based on Social, Economic, Cultural Interactions in the Slum Areas the City of Makassar - Haeruddin; Andi Surahman Batara; Idhar Darlis; Andi Rizki Amelia (Media Kesehatan Masyarakat Indonesia, 2020)
The highest number of Tuberculosis (TB) cases was in Southeast Asia with a percentage of 45%, followed by Africa 25%, West Pacific 17%, Middle East 7%, Europe 3% and American Countries 3%, while for the 5th rank, the highest Tuberculosis sufferers (56% world TB cases) are India, Indonesia, China, the Philippines and Pakistan. The purpose of this study was to observe the spread ofpulmonary tuberculosis through spatial analysis by observing the aspects of social, economic and cultural interactions in the slum areas of Makassar City. Currently, the analysis of the distribution of tuberculosis cases in Makassar City isstill in the form of aggregation, not in the form of mapping. This requiresidentification in the form of spatial analysis. This type of research is qualitative research with the in-depth interview method. The informants in the study were tuberculosis patients and were determined by Snowball Sampling. The results showed that pulmonary tuberculosis transmission based on spatial analysis in slum settlements showed that houses that were close to each other and hadsettlements that tended to be clustered had a greater risk of case transmission. Based on spatial analysis, there is diffusion of pulmonary TB cases in these residential areas. The diffusion pattern that occurs explains the addition of new cases over time. The diffusion pattern that occurs is a contagious diffusion type. Contagious Diffusion is an infection that spreads through direct contact of an individual infected with an infectious disease. Distance greatly affects the process of infectious disease transmission, so that if a person is close to the source of the infection, he will have a much greater probability of being infected when compared to individuals or areas far from the source of the disease.